The extent to which private schools in Shafa Badran area, Amman, implement their educational and legal obligations to apply online education in light of Corona pandemic - mahasneh, Omar musa; bnitaha, Othman Ibrahim (Arab Journal for Sciences and Research Publishing, 2020)
This study examines whether or not the outbreak of Corona Virus under the Jordanian Defense Law considers a legal impossibility "force majeure", and it determines the obligations of private schools in the online teaching with taking into account the satisfaction of students and their guardians. For this purpose, the descriptive survey approach has followed in this research by analyzing (34) questionnaires filled by the students’ guardians. From the educational side, the survey has reached that (97%) of the guardians prefer the direct/traditional teaching while (3%) prefer the online method; (65%) believe that the online teaching applied by the private schools did not take care of the various needs of students; (70%) think that non-direct communication (face to face) between the teachers and students was one of the main obstacles in the online teaching; and (90%) see that WhatsApp was the only online way for teaching the courses. From the legal side, the study has reached that the obligations of private schools changed from traditional teaching to online teaching because of the legal impossibility (majeure force) and the applied defense law. By other words, Unlike traditional teaching, the obligations of private schools have changed to online teaching and contacting as a new way since the outbreak of coronavirus.